Successful delayed-interval delivery in monochorionic diamniotic twin pregnancy: A case report - Tanja Baltus; Maria Luisa Martin (Elsevier, 2019)
Delayed-interval delivery in twin pregnancy is a rare occurrence. It is sometimes performed in twin pregnancies when the first twin is born at the limit of viabililty, to improve outcome for the second twin. It has been suggested that monochorionicity is a contraindication to delayed-interval delivery in multifetal pregnancy. The literature describes only a dozen cases over the last 20 years and only a handful of these reports specify success.We describe a case of a successful delayed-interval delivery of monochorionic diamniotic twins following prelabour rupture of membranes at 20 weeks of gestation. The first twin was previable, delivered at 23 weeks and 2 days of gestation, but the second twin was delivered at 24 weeks and 1 day of gestation and survived.Practitioners could consider delayed-interval delivery in monochorionic diamniotic twin pregnancy in a closely monitored environment if the first twin is born peri-viable, to obtain an improved outcome for the remaining fetus. Keywords: Delayed-interval delivery, Twin pregnancy, Monochorionic, Diamniotic